The Carbon Footprint of Fossil Power Plants and Potential Opportunities for Renewable Energy (Palm Oil Biodiesel) to Reduce Carbon Emissions in Indonesia - Lailatul Fajriyah; Yanif Dwi Kuntjoro; Sri Murtiana; Putri Azmi Millatie (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Power generator is one of sector that contributes to carbon emissions, because power plants in Indonesia are still dominated by the use of fuel. It is important to analyze the resulting carbon footprint to determine the extent of its impact, especially on the environment and its contribution to the greenhouse gas (GHG) effect, so that appropriate emission reduction measures can be identified. The method used is a literature study by collecting secondary data from the previous research existed in Indonesia. The average amount of carbon footprints are produced by Indonesia from fossil power plants (Coal, Natural Gas, and Diesel Fuel) in the last 5 years is 5538.11 KgCO2/MWh. The potential demand for electricity and the emissions resulted by-products will continue to increase every year, so solutions are needed best way to reduce emissions. Emission reduction can be resolved by increasing the use of New and Renewable Energy (NRE) as a raw material for Diesel Power Plants (DPT). The type of EBT used is biodiesel from palm oil. The carbon footprint of palm oil biodiesel production process is only 2281.66 KgCO2/MWh.  41% lower than that of fossil power plants. The push for NRE development needs to be further increased in order to reduce energy emissions and to achieve the target of using New and Renewable Energy (NRE) of at least 23% and 31% in 2025 and 2050. The type of EBT used is biodiesel from palm oil. The carbon footprint of palm oil biodiesel production process is only 2281.66 KgCO2/MWh.  41% lower than that of fossil power plants. The push for NRE development needs to be further increased in order to reduce energy emissions and to achieve the target of using New and Renewable Energy (NRE) of at least 23% and 31% in 2025 and 2050.